Early clinical manifestations associated with death from visceral leishmaniasis. - Valdelaine Etelvina Miranda de Araújo; Maria Helena Franco Morais; Ilka Afonso Reis; Ana Rabello; Mariângela Carneiro (PLoS Neglected Tropical Diseases, 2012)
Background In Brazil, lethality from visceral leishmaniasis (VL) is high and few studies have addressed prognostic factors. This historical cohort study was designed to investigate the prognostic factors for death from VL in Belo Horizonte (Brazil). Methodology The analysis was based on data of the Reportable Disease Information System-SINAN (Brazilian Ministry of Health) relating to the clinical manifestations of the disease. During the study period (2002-2009), the SINAN changed platform from a Windows to a Net-version that differed with respect to some of the parameters collected. Multivariate logistic regression models were performed to identify variables associated with death from VL, and these were included in prognostic score. Principal findings Model 1 (period 2002-2009; 111 deaths from VL and 777 cured patients) included the variables present in both SINAN versions, whereas Model 2 (period 2007-2009; 49 deaths from VL and 327 cured patients) included variables common to both SINAN versions plus the additional variables included in the Net version. In Model 1, the variables significantly associated with a greater risk of death from VL were weakness (OR 2.9; 95%CI 1.3-6.4), Leishmania-HIV co-infection (OR 2.4; 95%CI 1.2-4.8) and age ≥60 years (OR 2.5; 95%CI 1.5-4.3). In Model 2, the variables were bleeding (OR 3.5; 95%CI 1.2-10.3), other associated infections (OR 3.2; 95%CI 1.3-7.8), jaundice (OR 10.1; 95%CI 3.7-27.2) and age ≥60 years (OR 3.1; 95%CI 1.4-7.1). The prognosis score was developed using the variables associated with death from VL of the latest version of the SINAN (Model 2). The predictive performance of which was evaluated by sensitivity (71.4%), specificity (73.7%), positive and negative predictive values (28.9% and 94.5%) and area under the receiver operating characteristic curve (75.6%). Conclusions Knowledge regarding the factors associated with death from VL may improve clinical management of patients and contribute to lower mortality.